(untitled) (Research, Society and Development, 2020)
Study with the objective of analyzing the presence of cardiovascular risk factors and the perception of young adults about health. This is a descriptive, cross-sectional study with a qualitative component. Quantitative data collection took place between March and September 2017 and qualitative data between November and December 2018 included 129 young adults and 21 young adults in the qualitative stage, both in the 20-29 age group , from a city in the interior of Rio Grande do Sul. The quantitative data underwent descriptive statistical analysis and the production of qualitative data took place through semi-structured interviews, analyzed according to the content analysis technique proposed by Bardin. Young adults had sedentary lifestyle, smoking, obesity, alcohol and drug use, depression and stress as factors of cardiovascular risk. In addition, they demonstrated superficial knowledge about health and recognized healthy practices, but had difficulty in incorporating them into their daily lives. The present study brings an initial approach with young adults, opening paths for future deepening on the theme to occur, in order to contribute to the improvement of health care provided to young adults attended in Primary Health Care and to contribute to the planning of public policies aimed at this public.